Factors Associated With Falls Among Urban-Dwellers Aged 55 Years and Over in the Malaysian Elders Longitudinal Research (MELoR) Study - Alex, Deepa; Khor, Hui M.; Chin, Ai V.; Hairi, Noran N.; Cumming, Robert G.; Othman, Sajaratulnisah; Khoo, Selina; Kamaruzzaman, Shahrul B.; Tan, Maw P. (Frontiers in Public Health, 2020)
Falls are major issues affecting the older population with potentially serious complications, including fractures, head injury, institutionalization, fear of falling and depression. While risk factors for falls have been established across Western Europe and North America, geographical differences in falls risk have not been well researched. We aim to examine the clinical and physical risk factors for falls in a middle-income South East Asian country. Cross-sectional data from the Malaysian Elders Longitudinal Research (MELoR) study involving 1,362 community dwelling individuals aged 55 years and above was utilized. Information on sociodemographic and medical history was obtained by computer-assisted questionnaires completed during home visits and hospital-based detailed health checks. Univariate and multivariate analyses compared non-fallers and fallers in the previous 12 months. Urinary incontinence, hearing impairment, depression, arthritis and cognitive impairment were risk factors for falls in the past 12 months after adjustment for age in our study population. Awareness about the risk factors in a population helps the design of fall prevention strategies that target specific or multiple risk factors.